(untitled) (Revista Gestão & Conexões, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2012.1.1.4038.74-94 Portfolio Management entails the systematic evaluation, selection and prioritization of R&D projects in the organizational context. The aim of this article is to discuss the use of tools for managing the R&D portfolio in the Brazilian electricity sector, using the case study of an energy distribution company as an analytical support. In this sector, investment in research projects and guidelines for their completion are enforced by law. Otherwise, energy companies would not invest in R&D, they would rather buy equipment and systems from international suppliers. The execution of these projects is also strongly supervised by ANEEL, which guarantees that their results will turn into new products, patents, job creation, tariff reduction and operational efficiency for the company. If projects do not accomplish with government criteria, energy companies may be strongly penalized. In order to avoid such risk, companies may implement Portfolio Management tools.